After Parmenides idealism, realism, and epistemic constructivism - Rockmore, Tom, 1942- (The University of Chicago Press, 2021)
"In After Parmenides, Tom Rockmore takes us all the way back to the beginning of philosophy. Parmenides held that thought and being are one: what we know is what is. For Rockmore, this established both the good view that we should think of the world in terms of what the mind constructs as knowable entities as well as the bad view that there is some non-mind-dependent "thing"-the world, the real-which we can know or fail to know. No, Rockmore says: what we need to do is give up on the idea that there is any extra-mental "real" for us to know. We know and become acquainted with the objects of cognition that our mind constructs. After Parmenides illustrates the contest between variants of the "standard" view and variants of the "non-standard, constructivist view" in the history of philosophy, from Plato and Aristotle to Descartes and Locke, Leibniz, Spinoza, Hume, Kant, post-Kantians including Fichte, Hegel, and Schopenhauer, Marx, the early pragmatists, analytic philosophy, contemporary French speculative realism, and more. This ambitious but accessibly written book shows how new connections can be made in the history of philosophy when it is reread through a new lens"--